2018
DOI: 10.1039/c8cc05083j
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonium hydrogels for controlled release of ionic cargo

Abstract: We describe the synthesis of three different phosphonium salts and their reaction with poly(ethylene glycol) dimethacrylate to create cationic hydrogels. The hydrogels were loaded with an anionic dye and an anionic anti-inflammatory drug through ionic interactions and compared with an analogous ammonium gel. The release rates of these anions depended on their structure and pKa values, as well as the pH and ionic strength of the release medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…One of the most promising pathways for application of ionic polymeric materials in the biomedical fields regroups drug, 119,188,189 gene, 190,191 nucleic acid 192 and protein 193 delivery. Incorporating a zwitterionic sequence within polypeptides, 194 adding phosphonium groups into PEG-based hydrogels, 195 or functionalizing chitosan-PEG nanoparticles 196 are among recent strategies to design drug delivery systems. Besides, polyethyleneimines and phosphonium-based ionomers depict non-viral vectors to target tumors or cancers as they show high cellular uptake efficiency and easy assembly with small interfering RNA through electrostatic interactions.…”
Section: Applications Of Ionic Polymeric Materialsmentioning
confidence: 99%
“…One of the most promising pathways for application of ionic polymeric materials in the biomedical fields regroups drug, 119,188,189 gene, 190,191 nucleic acid 192 and protein 193 delivery. Incorporating a zwitterionic sequence within polypeptides, 194 adding phosphonium groups into PEG-based hydrogels, 195 or functionalizing chitosan-PEG nanoparticles 196 are among recent strategies to design drug delivery systems. Besides, polyethyleneimines and phosphonium-based ionomers depict non-viral vectors to target tumors or cancers as they show high cellular uptake efficiency and easy assembly with small interfering RNA through electrostatic interactions.…”
Section: Applications Of Ionic Polymeric Materialsmentioning
confidence: 99%
“…Monomers were synthesized by reacting triethylphosphine, triethylamine, tri­( n -butyl)­phosphine, tri- n -butylamine, and tris­(hydroxypropyl)­phosphine with 4-vinylbenzyl chloride to generate the corresponding salts ( Et-P , Et-N , Bu-P , Bu-N , and Hp-P ; Scheme ) as reported previously. Tris­(hydroxypropyl)­amine also reacted with 4-vinylbenzyl chloride, but the reaction did not proceed to completion, and upon work-up the products swelled extensively and could not be purified. Polymerization of the remaining monomers was performed in water at 60 °C using the thermal initiator VA-044 for 16 h. Conventional free-radical polymerization was chosen as it could provide high molar mass polymers .…”
Section: Resultsmentioning
confidence: 99%
“…Triethyl­(4-vinylbenzyl)­phosphonium chloride ( Et-P ), triethyl­(4-vinylbenzyl)­ammonium chloride ( Et-N ), tri­( n -butyl)­(4-vinylbenzyl)­phosphonium chloride ( Bu-P ), tri­( n -butyl)­(4-vinylbenzyl)­ammonium chloride ( Bu-N ), and tris­(hydroxypropyl)­(4-vinylbenzyl)­phosphonium chloride ( Hp-P ) were synthesized as previously reported. , Poly­[triethyl­(4-vinylbenzyl)­phosphonium chloride] ( P-Et-P ), poly­[tri­( n -butyl)­(4-vinylbenzyl)­phosphonium chloride] ( P-Bu-P ), and poly­[tris­(hydroxypropyl)­(4-vinylbenzyl)­phosphonium chloride] ( P-Hp-P ) were also synthesized as previously reported . Triethylamine, tributylamine, 4-vinylbenzyl chloride, fluorescein sodium salt, and D 2 O were purchased from Sigma-Aldrich and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…This trend also does not strictly follow the trends observed for hydrogel viscoelasticity or network morphology (ratio of tube structures to fibers/tapes), indicating that differences in the total amount of diclofenac released cannot be explained entirely by these emergent properties of the hydrogels. A recent study of release of diclofenac from positively charged phosphonium gels indicated that the diclofenac release profiles were unaffected by changes in pH, but diclofenac release was slower from hydrogels containing triphenylphosphine compared to hydrogels with nonaromatic phosphines . Presumably, aromatic diclofenac molecules participate in specific π–π interactions with aromatic triphenylphosphine that is not possible with nonaromatic phosphines.…”
Section: Drug Release Profiles From Cationic Fmoc-phenylalanine Deriv...mentioning
confidence: 99%
“…A recent study of release of diclofenac from positively charged phosphonium gels indicated that the diclofenac release profiles were unaffected by changes in pH, but diclofenac release was slower from hydrogels containing triphenylphosphine compared to hydrogels with nonaromatic phosphines. 68 Presumably, aromatic diclofenac molecules participate in specific π−π interactions with aromatic triphenylphosphine that is not possible with nonaromatic phosphines. This suggests that the molecular structure of the gelators in this study may play a role in the differences in the amount of diclofenac released at saturation.…”
Section: Acs Applied Bio Materialsmentioning
confidence: 99%